STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI SDN 02 ARGOSUKO PONCOKUSUMO - Dinatul Nur Karimah; Devi Wahyu Ertanti; Muhammad Sulistiono (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
Quality education is the key to building competent people and producing good graduates. High and low quality of education in schools is not only determined by the teacher and his competence, but also determined by the strategy or efforts of the principal in carrying out his leadership. This study aims to determine the strategies used by the head of SDN 02 Argosuko Poncokusumo in improving the quality of education. The research approach used by researchers is a qualitative research approach. The main data source was obtained from the subjects in this study, namely the principal. Data collection techniques used are through observation, interviews, and documentation. While the data analysis technique in this research is data collection, data condensation, data display, and conclusions drawing. The results of this study are the strategies used by the head of SDN 02 Argosuko Poncokusumo to improve the quality of education there are 5, namely: increasing human resources, conducting supervision, holding coordination meetings, evaluating teaching and learning activities, and fostering teacher discipline. The obstacles experienced by school principals in implementing this strategy, namely: lack of teacher discipline and limited infrastructure.